Rancang Bangun Sistem Informasi Akademik Pada Sekolah Perhotelan Hols Berbasis Website - Arief Yahya Prasetio; Eka Dyar Wahyuni; Abdul Rezha Efrat Najaf (Asosiasi Profesi Telekomunikasi dan Informatika Indonesia, 2024)
Faculty The Faculty of HOLS Hospitality School faces challenges in manual administration, such as accumulating registration data, difficulty in data retrieval, risk of data loss, administrative inaccuracies, and time-consuming registration and attendance processes, increasing the risk of administrative errors. To address these issues, researchers designed a web-based information system using the waterfall model and PHP programming language. This system allows students to mark attendance using a QR code within a 5-meter radius, mentors to reschedule classes quickly and easily, and administrators to control administrative data accurately and efficiently. The result of this research is an information system product that facilitates academic administration management at HOLS Hospitality School, supports e-learning facilities, and simplifies coordination between students, mentors, and administrators.